ANALISIS LOGIT KEPUTUSAN PERILAKU ILLEGAL FISHING NELAYAN PELABUHAN PERIKANAN NUSANTARA BRONDONG JAWA TIMUR - Clara Tiwiw; Daniel R. Monintja; Akhmad Fauzi; Kadarwan Soewardi; Victor P.H. Nikijuluw (Jurnal Teknologi Perikanan dan Kelautan, 2012)
Illegal fishing activities are basically not just done by foreign fisherman but also carried out by fisherman of Indonesia but they are using the size are smaller that is under 30 gross tonage. Due to the size a small fishing vessels are often allowed by the law enforcement officers due to the influence that is relatively small, whereas in the number of ships that are much smaller of course though its capacity would provide a major problem for the management of fish resources in Indonesia. Fishermen who settled in Brondong East Java is an example of illegal fishing activities as offeriders by loweinr the size of the ship that is lowering the gross tonage. These activities were carried out because the cost of maintaining a very troublesome permission and expensive.